Depression among caregivers of thalassemia children in two government hospitals in Klang Valley / Dr. Mastura Mat Rosly - Mat Rosly, Dr. Mastura (2020)
Background: Caregiving for patients with chronic diseases causes distress that predispose the caregivers to depression. Thalassemia is a chronic debilitating illness that is common in this country. It has been proposed that caregiving for children with thalassemia increases risk of developing depression. Objective: This study aims to determine the prevalence of Major Depressive Disorder among caregivers of children with thalassemia in Hospital Selayang and Hospital Sungai Buloh. It also aims to determine the associated factors of depression among the caregivers. Methodology: This is a cross-sectional study involving 64 caregivers of children with thalassemia under follow up at Hospital Selayang and Hospital Sungai Buloh. Those who fulfilled the inclusion criteria and gave informed consent were recruited. Caregivers’ sociodemographic, clinical and children’s clinical data were obtained from an interview with the caregivers and from the medical records. The diagnosis of Major Depressive Disorder was confirmed by Mini International Neuropsychiatric Interview (M.I.N.I.) for Major Depressive Episode. The level of caregiver strain was assessed using the Caregiver Strain Index (CSI) tool. Data was analysed using the Statistical Package for Social Sciences (SPSS) version 26. Results: The prevalence of depression among the caregivers is 17%. From bivariate analysis, factors found to be associated with depression were caregivers’ age (p= 0.155), marital status (p=0.177), education level (p=0.100), household income (p=0.176), financial support (p=0.006), history of death in the family (p=0.201), personal history of mental illness (p=0.172), duration of illness (p= 0.093), comorbidities (p=0.201) and high caregiver strain (0.001). From multivariate analysis the factor found to be significantly associated with depression is high caregiver strain (OR: 10.04, CI: 1.41-71.58, p= 0.021). Conclusion: High caregiver strain is a good predictor for depression among caregivers of children with thalassemia disease. Early recognition and intervention of depression among caregivers can improve quality of care for the children with thalassemia.